Conched Out: Total Reconstructed Fisheries Catches for the Turks and Caicos Islands Uncover Unsustainable Resource Usage - Ulman, Aylin; Burke, Lily; Hind, Edward; Ramdeen, Robin; Zeller, Dirk (Frontiers in Marine Science, 2016)
The Turks and Caicos Islands' total marine fisheries catches were estimated for 1950–2012 using a catch reconstruction approach, estimating all removals, including reported catch destined for export, and unreported domestic artisanal and subsistence catches. Total reconstructed catch for the period is approximately 2.8 times that reported by the Turks and Caicos to the FAO, and 86% higher than the export-adjusted national reported baseline. The pattern of total catches (strong decline to 1970, followed by gradual increase) differs distinctly from that shown by data reported to FAO. Reported landings show a steady increase from less than 1000 t·year−1 in the 1950s to around 6000 t·year−1 in the 2000s. In contrast, the total reconstructed catches suggest declines in total catches from around 20,000 t in 1950 to a low of about 5000 t in 1970, before gradual increases to about 12,500 t·year−1 in the late 2000s. Major discrepancies between reported and reconstructed data are under-reported artisanal catches in the early decades (accounting for 86% of total catches), and the absence of subsistence catches (14% of total catches) in reported data. Queen conch (Strombus gigas) and Caribbean spiny lobster (Panulirus argus) dominate reconstructed catches. No discards were estimated as fishing has been highly selective, carried out by hand collection (conch), trap or hook (lobster), or hook and line (finfish). New data published here from local seafood consumption surveys demonstrates that the total local consumption of conch equates to almost the entire total allowable catch, before exported amounts are even factored. Policy-makers in the Turks and Caicos need to act if the sustainability of the fisheries stock and fishing industry is to be ensured.